Lupins as a Raw Material for Human Foods and Animal Feeds - D.S. Petterson; A.H. Fairbrother (Indonesian Food and Nutrition Progress, 1996)
The seeds or grain of lupins, a cool climate legume, are a rich source of protein and energy. They could prove a valuable alternative to soybean and dry peas for both human foods and animal feeds. One advantage would be that lupins have a lower content of antinutritional factors, particularly the protease inhibitors and lectins. Lupins are a good substrate for fermentation and can be used to make tempe and traditional fermented foods for Japan, Korea and China. Lupin flour can be added to wheat flour to make high protein breads, cakes and pas¬tas of higher nutritional value. Lupins can also be pro¬cessed to make a protein concentrate, and a dietary fi¬bre fraction with excellent water-holding capacity. Lupins have been shown to be a useful ingredient in the diets of fish and crustaceans, pigs, poultry and dairy and beef cattle. Much work to adapt its use for Indone¬sian conditions will be needed before the respective in¬dustries can fully benefit from this new commodity